The Role of Using Micro-Leaning Strategy through Instagram to Develop Lifelong Learning Skills for Adults - Alshafei, Wed Khaled; Fathi, Anwar Wahid; Mujallid, Amjaad Tariq (Journal of Curriculum and Teaching Methodology, 2024)
The study aimed to find the role of using the micro-learning strategy through Instagram to develop lifelong learning skills for adults. Use the descriptive method, for random sample of308 adults from Instagram users, in the Kingdom of Saudi Arabia, using questionnaire. As a result, there were statistically significant differences between the averages of these skills in favor of males, age and to the educational level for communication and sharing skills, and in favor of times of using social media. And there were no differences in personal knowledge management skills, dealing with digital content, and self-direction, which are attributed to the educational level variable. It also showed correspondence towards the skill of managing personal knowledge in terms of accessing and evaluating knowledge, applying, and developing knowledge, transferring knowledge and securing information, as well as towards the skill of dealing with digital content, also towards the skill self-direction in terms of planning, implementation, monitoring, evaluation and reflection, communication skill and share. It also shows the role of using Instagram as an electronic learning environment. It is a tool that the learner likes and is easy to use. It also supports access to information and access to creative ideas. The micro-learning strategy also contributed to the ease of information delivery, as well as ensuring that the learner gets the desired benefit of fully displayed content. The study recommends including lifelong learning skills for adults in educational institutions, developing lifelong learning skills for adults to match the requirements of the labor market, and employing social networks in educational institutions.